2007
DOI: 10.1080/08820130701360972
|View full text |Cite
|
Sign up to set email alerts
|

ExperimentalLeishmania (L.) amazonensisLeishmaniasis: Characterization and Immunogenicity of Subcellular Fractions

Abstract: A technique developed in Trypanosoma cruzi biochemical studies was successfully used to fractionate Leishmania (Leishmania) amazonensis promastigotes. Ultrastructural analyses revealed a membrane fraction (MF) associated to subpellicular microtubules, a ribosomal-rich microsomal fraction (MicF), and a flagellar fraction (FF) free of associated membrane. All fractions proved to be immunogenic through delayed type hypersensitivity reaction assays. Therefore, a protocol was designed to test whether these fraction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…(c) Isolation of the microsomal fraction. Leishmania amazonensis promastigotes were submitted to subcellular fractioning in water/ice bath as previously described (Zaverucha do Valle et al 2007). Parasites were washed with PBS+2% glucose, re-suspended with 20 m m Tris-HCl, pH 7·4, 12·5 m m sucrose, incubated for 20 min, and mechanically disrupted by a Douncer homogenizer in the presence of 10% non-ionic detergent Lubrol PX to produce the total protein extract (ET).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(c) Isolation of the microsomal fraction. Leishmania amazonensis promastigotes were submitted to subcellular fractioning in water/ice bath as previously described (Zaverucha do Valle et al 2007). Parasites were washed with PBS+2% glucose, re-suspended with 20 m m Tris-HCl, pH 7·4, 12·5 m m sucrose, incubated for 20 min, and mechanically disrupted by a Douncer homogenizer in the presence of 10% non-ionic detergent Lubrol PX to produce the total protein extract (ET).…”
Section: Methodsmentioning
confidence: 99%
“…Supernatant (6 ml) was layered on top of 2 ml of buffer containing 20% sucrose, 10 m m MgCl 2 , 25 m m KCl , and 10 m m Tris-HCl, pH 7·4, and centrifuged at 100 000 g for 30 min to produce the microsomal fraction (micF), which contains endoplasmic reticulum-derived vesicles, including ribosomes (Zaverucha do Valle et al . 2007).…”
Section: Methodsmentioning
confidence: 99%
“…Immunological findings against Leishmania amazonensis infection in the murine model highlight is a strong tool for proposing immunology profiles and vaccines for cutaneous leishmaniasis [ 4 , 5 ]. In this context, previous studies with subcellular fractionation of L. amazonensis promastigote forms have shown that the microsomal fraction (FMic) associated with immunomodulators provides protection against experimental infection by this parasite [ 6 ]. Furthermore, analyses of the different components of the fraction allowed for the identification of Leishmania spp.…”
Section: Introductionmentioning
confidence: 99%